1992
DOI: 10.1002/bscb.19921010707
|View full text |Cite
|
Sign up to set email alerts
|

New Fused as‐Triazines with Bridgehead Nitrogen Synthesis and Reactivity

Abstract: Two synthetic pathways have been elaborated for,the synthesis of py~ido[l,2-b]-as-triazinium salts and were also extended to the linearly fused as-triazino [2,3-b]isoquinolin1um and the angularly fused as-triazino[3,2-a]isoquinolinium systems. The ring closures were found to proceed in regioselective manner which was rationalized by assumption of the different charge distribution in acidic and basic conditions. Preparative route has also been worked out for the synthesis of pyrido[2,l-fl-as-triazinium salts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Enamines, ketene‐ N , N ‐acetals, O , O ‐acetals, and N , S ‐acetals and other electron‐rich alkenes reacted with 1,2,4‐triazines as dienophiles to cause transformation of the ring via inverse electron‐demand Diels–Alder cycloaddition reactions . Thus, the reaction of 3,5,6‐triphenyl‐1,2,4‐triazine ( 10 ) with the enamine 13 gave the adduct 14 via the addition reactions to C ‐5 of 1,2,4‐triazine ring (Scheme ) .…”
Section: ‐Alkyl/aryl/heteroaryl‐56‐diphenyl‐124‐triazinesmentioning
confidence: 99%
“…Enamines, ketene‐ N , N ‐acetals, O , O ‐acetals, and N , S ‐acetals and other electron‐rich alkenes reacted with 1,2,4‐triazines as dienophiles to cause transformation of the ring via inverse electron‐demand Diels–Alder cycloaddition reactions . Thus, the reaction of 3,5,6‐triphenyl‐1,2,4‐triazine ( 10 ) with the enamine 13 gave the adduct 14 via the addition reactions to C ‐5 of 1,2,4‐triazine ring (Scheme ) .…”
Section: ‐Alkyl/aryl/heteroaryl‐56‐diphenyl‐124‐triazinesmentioning
confidence: 99%
“…The chemical transformations concerning us here are depicted in Scheme . Literature survey has revealed that linearly fused tricyclic triazinium salts are usually prepared from α-diaminoisoquinolinium salts and α-dioxo compounds.…”
mentioning
confidence: 99%